Enhanced binomial method for hyperfine field distributions of the mechanically alloyed Fe-Si system (2006)
ABSTRACT: Fe1-qSiq alloys, with 0.03 ≤ q ≤ 0.3, were prepared employing mechanical alloying with milling times ranging from 15 to 75 hours. Magnetic and structural properties of the samples were followed by means of 57Fe Mössbauer spectroscopy and X-ray diffraction. The hyperfine field distributions obtained from fitting the Mössbauer spectra were modeled by using an enhanced binomial method, which includes a new parameter accounting for the different degrees of disorder that the milling procedure can induce. The method employed allows obtaining both, the most probable configurations as well as the hyperfine field fractional changes originated by the atomic environment within the first three Fe coordination shells as the silicon concentration is increased. Results involving compositional and milling time dependence of the Mössbauer parameters and those used in our model are also presented and discussed.